Causes analysis on cracks in nickel-based single crystal superalloy fabricated by laser powder deposition additive manufacturing. (15th December 2018) - Zhou, Zhipeng; Huang, Lan; Shang, Yijing; Li, Yunping; Jiang, Liang; Lei, Qian
Abstract: Additive manufacturing is an advanced forming method to fabricate complex components, while cracks appear in the deposited nickel-based single crystal superalloy samples undesirably. Though fabrication of crack-free superalloy were reported, effective solutions to fabricate crack-free nickel-based single crystal superalloy samples are still uncovered, thus the additive manufacturing in single crystal superalloy is still an extremely difficult work. In this work, we fabricated nickel-based single crystal superalloy samples through laser powder deposition, and analyzed the causes of crack during deposition processing. Experimental results demonstrate that the as-deposited thin-wall samples presented single crystal structure and its crystal orientation is well aligned with the [001] orientation of substrate, while some cracks appeared in the as-deposited block samples. Large misorientation angle in the local regions played significant roles in the cracks initiation and the further cracking propagation. Solidification cracks are attributed to the shrinkage cavities and the high-melting point interdendritic carbides, while liquation cracks are attributed to the low melting point compounds. These findings give a guide for causes analysis on cracks in the nickel-based single crystal superalloy fabricated by laser powder deposition additive manufacturing, which has bright prospects in single crystal superalloy manufacturing and repair. Graphical abstract: Highlights: Nickel-based single crystal superalloy samples were fabricated through laser powder deposition. Large misorientation angle played significant roles in the cracks initiation and the further cracking propagation. These findings give a guide for causes analysis on cracks in the nickel-based single crystal superalloy.